DepRescribing inapprOpriate Proton Pump InhibiTors (DROPIT): study protocol of a cluster-randomised controlled trial in Swiss primary care - Stefan Neuner-Jehle; Katharina Tabea Jungo; Sven Streit; Sven Trelle; Nicolas Rodondi; Carole Elodie Aubert; Kristie Rebecca Weir; Enriqueta Vallejo-Yagüe; Samantha Chan; Marie Roumet; Pascal Juillerat; Sofia Carolina Zambrano Ramos; et al. (BMJ Open)
Objectives Proton pump inhibitors (PPIs) are widely prescribed medications and commonly used for the treatment of gastric acid-related disorders. Nevertheless, PPIs are often overused leading to potential adverse effects and unnecessary healthcare costs. Deprescribing strategies have emerged to safely reduce or substitute inappropriate PPIs and optimise patient care in an evidence-based manner. This protocol describes a study to evaluate the effectiveness of a PPI deprescribing intervention in comparison to usual care in the Swiss primary care setting.Design An open-label, cluster randomised controlled trial.Setting Swiss primary care settings.Participants Included participants will be adults with inappropriate PPI treatment and will be recruited by general practitioners (GPs). Participants treated by the same GP constitute a cluster. Clusters are randomised 1:1 to either the intervention group or the control group.Interventions The intervention components consist of deprescribing tools including educational material, decision aids for both participants and GPs, and additional trainings for GPs only. Patients in the control group will receive usual care. Data will be collected at baseline, 3-, 6-, 9- and 12-month follow-up time through online surveys or a phone call for both GPs and participants.Primary and secondary outcome measures The first co-primary endpoint is the effectiveness of the deprescribing intervention measured by the change of prescribed PPI dose. The second co-primary endpoint is safety, which is measured with the Reflux Disease Questionnaire assessing change in gastrointestinal symptoms. There are several secondary endpoints, such as the total number of prescribed medications, occurrences of changes in prescription patterns, PPI discontinuation and cost-effectiveness.Conclusions The findings from this study will provide evidence on the effectiveness and safety of a PPI deprescribing intervention for patients and GPs. Successful implementation of our PPI deprescribing strategy has the potential to improve patient outcomes and lower costs.Trial registration number NCT06129474.